2014
DOI: 10.12973/jesr.2014.41.3
|View full text |Cite
|
Sign up to set email alerts
|

Daily life subjects that can be used with context based learning in high school physics lessons

Abstract: ÖZET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Gilbert (2006) stated in study that cognitive level and experiences should be taken into account in the selection of contexts in teaching processes. Cetin (2014) reported that context-based learning and the contexts selected from daily life were different between the class levels. Yesildere (2006) reported that there were certain differences between the paths that the students follow in mathematical thinking and knowledge acquisition processes in different class levels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Gilbert (2006) stated in study that cognitive level and experiences should be taken into account in the selection of contexts in teaching processes. Cetin (2014) reported that context-based learning and the contexts selected from daily life were different between the class levels. Yesildere (2006) reported that there were certain differences between the paths that the students follow in mathematical thinking and knowledge acquisition processes in different class levels.…”
Section: Conclusion and Discussionmentioning
confidence: 99%